The Lao Cookstove Experience : Redefining Health through Cleaner Energy Solutions - Dave, Rutu; Balasundaram, Rema N. (World Bank, Washington, DC, 2016)
Redefining Health through Cleaner Energy Solutions. In the Lao People’s Democratic Republic household air pollution from the incomplete combustion of solid fuels is the top health risk, costing some 3.5 percent of GDP in lost productivity. To increase access to modern cooking and heating solutions in East Asia, the World Bank introduced a Clean Stove Initiative in 2012. Pilot projects were begun in China, Indonesia, and Mongolia, as well as Lao PDR. One of the first challenges was the need to bring all relevant ministries and stakeholders on board to help recognize the urgency of the problem and the magnitude of suffering that was occurring as a result of household air pollution. The other was to link the health situation with the need for a clean energy solution.